2017
DOI: 10.1371/journal.pone.0182320
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying kinematic differences between land and water during squats, split squats, and single-leg squats in a healthy population

Abstract: Aquatic exercises can be used in clinical and sporting disciplines for both rehabilitation and sports training. However, there is limited knowledge on the influence of water immersion on the kinematics of exercises commonly used in rehabilitation and fitness programs. The aim of this study was to use inertial sensors to quantify differences in kinematics and movement variability of bodyweight squats, split squats, and single-leg squats performed on dry land and whilst immersed to the level of the greater troch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…The studies analyzed reported the number of male and female participants, their age, height, and body mass. The study by Fantozzi et al [12] reported that the participants were healthy (males and females), and Severin et al [16] reported such data per sex. Other studies split the participants into healthy or with some pathology (in that study, particular cases had chronic anterior knee pain) and did not mention the participants' sex [15].…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies analyzed reported the number of male and female participants, their age, height, and body mass. The study by Fantozzi et al [12] reported that the participants were healthy (males and females), and Severin et al [16] reported such data per sex. Other studies split the participants into healthy or with some pathology (in that study, particular cases had chronic anterior knee pain) and did not mention the participants' sex [15].…”
Section: Participantsmentioning
confidence: 99%
“…Moreover, the authors provided information about the three kinds of usage that each sensor has: (i) accelerometer (range: ±2 g, ±6 g; bandwidth: 50 Hz; resolution: 14 bit; noise: 128 ug/ . Two other studies used five sensors (tri-axial accelerometer and gyroscope) with an acquisition frequency of 100 Hz [15,16]. None of the four selected studies report any kind of information about the sensors' sealing.…”
Section: Sensor Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Although many studies have reported that one-leg squat has various advantages in functional activities, no study has studied the effect of muscle activity on ankle stability. Therefore, the objective of this study was to investigate the effect of two types of single-leg squat exercise commonly used in clinical practice for strengthening and rehabilitation of lower limbs on muscles activity of the tibialis anterior (TA), peroneus longus (PL), and tibialis posterior (TP).…”
Section: -13mentioning
confidence: 99%